Therapeutic agency, in-session behavior, and patient-therapist interaction - Huber, Julia; Born, Ann-Kathrin; Claaß, Christine; Ehrenthal, Johannes C.; Nikendei, Christoph; Schauenburg, Henning; Dinger, Ulrike (Journal of clinical psychology, 2019)
Objective The aim of this study was to investigate associations between patients’ subjective agency, their observable in-session behavior, and the patient-therapist interaction during the early phase of psychotherapy. Methods The sample included 52 depressed patients in psychodynamic psychotherapy. After Session 5, the patients’ agency and the quality of the therapeutic alliance were assessed. Based on session recordings, two independent observers rated the patients’ involvement, their interpersonal behavior, and the therapists’ directiveness. Results Higher agency was associated with stronger therapeutic alliances. Patients who indicated higher agency in their therapy participated more actively in the session and showed less hostile impact messages. Patients’ agency was not related to therapists’ directiveness. Conclusions Patients’ sense of agency in psychotherapy was associated with more active involvement and affiliative interaction. The findings support the idea that patients need to feel capable of acting within and having an influence on their therapy to benefit from it.
First published: 14 September 2018
Gesehen am 22.07.2019